Analisis Closed-Loop Supply Chain pada Sistem Hidroponik Tanaman Kangkung Berbasis Boicyclofarming di Desa Balongsari - Firdaus, Ainur; Azzahra, Syavita Nur; Solikin, Syahrul Rahmadtulloh Putra; Afkar, Taswirul; Ahmad, Nuril; Ramadhani, Rahmad Syaiful (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
Limited agricultural land and increasing demand for food have encouraged the implementation of efficient and sustainable production systems. Biocyclofarming-based hydroponic systems are an alternative because they optimise the use of water, nutrients and biological waste in a closed cycle. This study aims to analyse the application of Closed-Loop Supply Chain (CLSC) in a water spinach hydroponic system in Balongsari Village. The study was conducted through supply chain flow mapping, crop productivity analysis, calculation of total supply chain cost structure, and evaluation of biological waste return flow as production input. The research object included local-scale water spinach hydroponic production units. The results showed that the application of CLSC was able to effectively integrate forward and reverse flows, increase resource use efficiency, and reduce system waste. Economically, the identified cost structure supported fair pricing and the sustainability of hydroponic businesses.